Indonesia and Malaysia Halal Certification Policy:Opportunities and Challenges - Fawa’id, Muhamad Wildan; Mutafarida, Binti (Journal of social Philantrophy and Halal Research, 2024)
This study explores the Halal Certification Policy in Indonesia and Malaysia, along with the opportunities and challenges faced in developing the halal industry. Despite Indonesia having the largest Muslim population in the world, Malaysia continues to hold the top position in the State of Global Islamic Economy (SGIE) rankings. This research identifies the factors contributing to Malaysia’s dominance, including an organized certification system, government support, and a robust halal infrastructure. Meanwhile, Indonesia encounters challenges such as harmonizing international standards, certification costs for small enterprises, and developing an integrated halal ecosystem. Through a qualitative descriptive approach, this study examines Indonesia’s SGIE achievements in the halal food sector, Islamic finance, fashion, Muslim-friendly tourism, cosmetics, and media. This research is significant in providing strategic insights for enhancing halal certification policies and practices in Indonesia, as well as strengthening its position in the global halal industry.